2005
DOI: 10.1111/j.1365-294x.2005.02520.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and nuclear DNA phylogeography of European grayling (Thymallus thymallus): evidence for secondary contact zones in central Europe

Abstract: Mitochondrial and microsatellite DNA markers were applied to infer the phylogeography, intraspecific diversity and dynamics of the distributional history of European grayling (Thymallus thymallus) with focus on its central and northern European distribution range. Phylogenetic and nested clade analyses revealed at least four major mtDNA lineages, which evolved in geographical isolation during the Pleistocene. These lineages should be recognized as the basic evolutionary significant units (ESUs) for grayling in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
137
3
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(162 citation statements)
references
References 78 publications
21
137
3
1
Order By: Relevance
“…As expected, CR haplotypes of reference samples from the Sava populations OBR and RAD entirely clustered into the SV clade (Da22, Da23, Weiss et al, 2002;Da34, Meraner and Gandolfi, 2012), while the Rhine River reference sample was fixed for RH genetic variants (At14, Weiss et al, 2002; AT26, GenBank acc. n. AY841359, in Gum et al, 2005;At27, Meraner and Gandolfi, 2012; At29, new haplotype, Genbank accession: JX961600) (see Online Resource 1). The At29 haplotype sequence was characterised by the occurrence of a four-fold 82 bp repeat in the right domain of the control region, as previously described for different RH haplotypes from the same drainage (Weiss et al, 2002;Gum et al, 2005).…”
Section: > Molecular Techniques and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, CR haplotypes of reference samples from the Sava populations OBR and RAD entirely clustered into the SV clade (Da22, Da23, Weiss et al, 2002;Da34, Meraner and Gandolfi, 2012), while the Rhine River reference sample was fixed for RH genetic variants (At14, Weiss et al, 2002; AT26, GenBank acc. n. AY841359, in Gum et al, 2005;At27, Meraner and Gandolfi, 2012; At29, new haplotype, Genbank accession: JX961600) (see Online Resource 1). The At29 haplotype sequence was characterised by the occurrence of a four-fold 82 bp repeat in the right domain of the control region, as previously described for different RH haplotypes from the same drainage (Weiss et al, 2002;Gum et al, 2005).…”
Section: > Molecular Techniques and Data Analysismentioning
confidence: 99%
“…n. AY841359, in Gum et al, 2005;At27, Meraner and Gandolfi, 2012; At29, new haplotype, Genbank accession: JX961600) (see Online Resource 1). The At29 haplotype sequence was characterised by the occurrence of a four-fold 82 bp repeat in the right domain of the control region, as previously described for different RH haplotypes from the same drainage (Weiss et al, 2002;Gum et al, 2005). Such a feature has been reported as being common among different salmonids (Sell and Spirkovski, 2004).…”
Section: > Molecular Techniques and Data Analysismentioning
confidence: 99%
“…This means that many organisms display complex phylogeographic structure with respect to current drainage patterns (e.g. ŠLECHTOVA et al, 2004, GUM et al, 2005. While this makes the region zoogeographically interesting, it also can cause some problems in trying to distinguish between natural and human-related mechanisms responsible for the distribution of genetic variation within and among river systems (WEISS et al, , 2002a.…”
Section: Regional Considerations On Freshwater Organisms (Central Eurmentioning
confidence: 99%
“…The European grayling is widely distributed in northern and continental Europe from the Ural mountains to the British Isles (Northcote 1995), and its phylogeography has been studied intensively analysing both mitochondrial data and microsatellites (Koskinen et al 2000(Koskinen et al , 2002Gum et al 2005). Koskinen et al (2000) found three main assemblages of mitochondrial haplotypes that diverged before the late Pleistocene, and it was concluded that Northern Europe was colonized from at least two ancient refugia.…”
Section: Introductionmentioning
confidence: 99%
“…Koskinen et al (2000) found three main assemblages of mitochondrial haplotypes that diverged before the late Pleistocene, and it was concluded that Northern Europe was colonized from at least two ancient refugia. Grayling populations in the UK were shown to be closely related to haplotypes from the River Rhine, Germany (Gum et al 2005).…”
Section: Introductionmentioning
confidence: 99%